Exploring the Concept of Wahdatul Wujud Ibn Arabi: Potential Solutions for Juvenile Delinquency in Indonesia - Regita Ayu; Anggi Afrina Rambe; Muhammad Nurfaizi Arya Rahardja; Annisa Ningtias Cevie Putri; Aceng Kosasih; Agus Fakhruddin (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
This research aims to analyze the concept of Ibn Arabi's wahdatul wujud as a Muslim scientist so that it can become a reference in the world of education to shape the character of students. Then the method used in this research is qualitative with a literature study approach, to describe the results of Ibn Arabi's extraordinary thoughts as a guide in character education, data collection techniques using data collection taken from books, journals and writings related to the research. Next, the data that has been collected is analyzed using text content in the form of words, images, symbols, ideas and themes in the form of messages in SDN Kertamukti III. The research results show that the concept of wahdatul wujud is very helpful in shaping students' character, such as awareness of unity, tolerance and acceptance, personality development, involvement in goodness and development of spiritual awareness. With the concept of wadatul wujud which provides an understanding that the relationship between humans and God is a unity that cannot be separated. Therefore, it is important for teachers to provide the concept of wahdatu wujud in education so that students understand the meaning of existence as a creature and reality in the world which is a manifestation of God Almighty.